ANALISIS DAN IDENTIFIKASI RISIKO KECELAKAAN KERJA PADA LANTAI PRODUKSI DI PERUSAHAAN AGROINDUSTRI MENGGUNAKAN JOB SAFETY ANALYSIS - Lubis, Rizki Fadhillah; Mendoza, Muhammad Dominique; Wijaya, Kinanti; Melati, Rima; Pulungan, Abraham Ismail (Politeknik ATI Padang, 2024)
As one of the largest agro-industrial companies in Indonesia engaged in the animal feed industry, it certainly has good Occupational Health and Safety standards. However, throughout 2022, this industry still experienced work accidents, especially in the production process. Work accidents that occur are at mild to moderate levels. Seeing this condition, it is deemed necessary to make efforts to prevent and minimize the risk of work accidents, one of which is using Job Safety Analysis. The Job Safety Analysis (JSA) method is used to identify hazards in the production process and provide suggestions for preventive measures. Based on the results of the job safety analysis, activities in the machinery sector and machine maintenance processes have a risk of work accidents such as being hit by boiler sparks, slipping, being pinched, and others. Strict supervision is needed for operators to wear personal protective equipment before working, ensuring that operators follow work instructions and standard operating procedures in working so that the risk of work accidents can be minimized.